IMPLEMENTASI PROGRAM SMART LIVING DI KELURAHAN SEMANGGI KECAMATAN PASAR KLIWON KOTA SURAKARTA - Khusnul Qotimah, Muwina; Suguyarti, Riris (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
As many as 70% of Indonesia's population in 2045 is estimated to live and live in cities, a smart city concept is needed that can provide a livable place to live for the community and increase the efficiency of public services. Smart Living is a relevant concept to be applied in conditions like this, a livable and clean environmental management will create a hygienic and efficient urban life for the community service itself. The purpose of this study is to analyze and describe how the Smart Living Program is Implemented in Semanggi Village, Pasar Kliwon District, Surakarta City. The analysis of the implementation of the Smart Living program in Semanggi Village, Pasar Kliwon District, Surakarta City uses George C. Edward III's implementation theory, there are 4 indicators of the success of an implementation in this theory, namely, Communication, Resources, Disposition, and Bureaucratic Structure. From the research conducted, it can be concluded that the implementation of the smart living program in Semanggi Village has been going well but there are still obstacles for the library that has not been inaugurated so that it is stalled and there is a lack of public awareness of the cleanliness of the surrounding environment. Therefore, it is necessary for the local government to conduct further communication through socialization to the community in increasing awareness of the revitalized environment.Keywords: Implementation, Smart Living, Smart City, Public Policy.